2007
DOI: 10.1128/jcm.02015-06
|View full text |Cite
|
Sign up to set email alerts
|

Serotype 1 and 2 Bovine Noroviruses Are Endemic in Cattle in the United Kingdom and Germany

Abstract: The genomically and antigenically distinct bovine noroviruses Bo/Jena/1980/DE and Bo/Newbury2/1976/UK have been associated with calf diarrhea. In the present seroprevalence study, both were found to be endemic in cattle from Germany and the United Kingdom, a finding in contrast to previous virus prevalence studies. They were less common than group A rotaviruses, particularly in calves, suggesting a different epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
(38 reference statements)
0
7
0
1
Order By: Relevance
“…No HuNoV sequences were identified despite the use of two primer sets designed for their detection, suggesting at least a very low prevalence of these human viruses in cattle. Despite the variety of the primers used in the present study, the lack of detection of the genotype 1 BoNoV could be explained by suboptimal primer use for the RT-PCR (Oliver et al, 2007b). The age of the cattle population studied was also suggested as an explanation for the lower detection of genogroup III genotype 1 NoV (Oliver et al, 2007b).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…No HuNoV sequences were identified despite the use of two primer sets designed for their detection, suggesting at least a very low prevalence of these human viruses in cattle. Despite the variety of the primers used in the present study, the lack of detection of the genotype 1 BoNoV could be explained by suboptimal primer use for the RT-PCR (Oliver et al, 2007b). The age of the cattle population studied was also suggested as an explanation for the lower detection of genogroup III genotype 1 NoV (Oliver et al, 2007b).…”
Section: Discussionmentioning
confidence: 75%
“…Despite the variety of the primers used in the present study, the lack of detection of the genotype 1 BoNoV could be explained by suboptimal primer use for the RT-PCR (Oliver et al, 2007b). The age of the cattle population studied was also suggested as an explanation for the lower detection of genogroup III genotype 1 NoV (Oliver et al, 2007b). As RT-PCR primers used in this study only target the viral polymerase region and thus miss potential recombinant strains, the possibility that some positive samples contained chimaeric bovine noroviruses could be another explanation for the low apparent prevalence of GIII.1 noroviruses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent serological study indicates that both Newbury2-like (GIII/2) and Jena-like (GIII/1) strains are common in the United Kingdom and Germany (Oliver et al, 2007b). However, cross reactions between shared epitopes of different genogroups and genotypes of noroviruses, which may complicate the assessment of serological surveys, have been described (Batten et al, 2006;Oliver et al, 2006b;Shiota et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies with more specific and sensitive detection reagents have shown that NoVs are frequent in husbandry animals worldwide (14,18,48,49,53,65,68,73). The existence of animal NoVs is relevant in several ways.…”
mentioning
confidence: 99%